2016
DOI: 10.1111/tid.12569
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of adenovirus (ADV)‐specific T cells in a boy with ADV pneumonia and disseminated disease after lung transplantation

Abstract: Human adenovirus (ADV) infections are the cause of severe morbidity and mortality in transplant recipients. Cidofovir (CDV) is the current standard antiviral treatment. We report the case of a 3-year-old boy after lung transplantation with severe ADV sepsis, who was monitored for ADV-specific T cells during his disease and recovery. A strong increase in ADV-specific T cells was accompanied by resolution of ADV in blood and bronchoalveolar lavage fluid. Antiviral treatment with CDV was individually adapted acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…123,127,128 Infection in lung recipients is common (up to 22% in 1 series) and there are multiple reports of severe infection, including graft loss, progression to BOS, and death. 125,[129][130][131][132] Infection in HSCT recipients can be severe and associated with significant mortality. In 14 adult HSCT recipients with adenovirus viremia, most of whom were treated with antivirals, almost 50% developed invasive adenoviral disease and 23% died of the infection.…”
Section: Adenovirusmentioning
confidence: 99%
“…123,127,128 Infection in lung recipients is common (up to 22% in 1 series) and there are multiple reports of severe infection, including graft loss, progression to BOS, and death. 125,[129][130][131][132] Infection in HSCT recipients can be severe and associated with significant mortality. In 14 adult HSCT recipients with adenovirus viremia, most of whom were treated with antivirals, almost 50% developed invasive adenoviral disease and 23% died of the infection.…”
Section: Adenovirusmentioning
confidence: 99%
“…Cytokines, chemokines [15,16] ImmunoKnow-Assay [17][18][19][20][21] TorqueTenoVirus [16,[22][23][24][25][26][27][28][29] Virus-specific T cells [30][31][32][33][34] Ahlenstiel-Grunow and Pape Molecular and Cellular Pediatrics (2021) 8:8…”
Section: Methods Studiesmentioning
confidence: 99%
“…Some data on ADV-specific T cells was generated by ELISpot in a small group of children after liver transplantation [50]. In one child with ADV pneumonia, ADV-specific T cells were measured after lung transplantation and the possibility of steering antiviral therapy using ADV-specific T cells is reported [11]. In our own cohort of 37 pediatric kidney recipients aged between 1 and 17 years (median 13 years), the pretransplant prevalence of ADV-specific CD4 T cells was 76% (data not published) without any ADV-associated complications after kidney transplantation.…”
Section: Adenovirus-specific T Cellsmentioning
confidence: 99%
“…Virus-specific T cells have been shown to play a significant role in control of virus replication [7]: Virus-specific CD4positive T cells detect viral epitopes which are presented on major histocompatibility complex (MHC) class II molecules on antigen-presenting cells such as B lymphocytes, dendritic cells and macrophages, and CD8-positive T cells locate and destroy virus-infected cells which present viral antigens by MHC class I molecules. Several studies, mainly in adults, have shown that the number of virus-specific T cells is associated with the risk of virus-specific complications [8][9][10][11][12][13][14][15][16][17][18][19]. Therefore, prophylaxis, diagnosis, and treatment of viral infections after kidney transplantation may be improved by the implementation of virus-specific T cells in routine monitoring [7].…”
Section: Introductionmentioning
confidence: 99%